Method for preparing high-entropy boride ultrahigh-temperature ceramic powder by liquid phase method

Through the liquid phase method combined with boron heat/carbon heat reduction reaction, transition metal oxides, boric acid and sorbitol are used as raw materials to perform gelation treatment, which solves the problem of uneven composition of high-entropy boronide ceramics and damage performance of oxidative impurities. Achieve efficient and low-cost ceramic powder preparation.

CN119430950AActive Publication Date: 2025-02-14WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411532711.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-14
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The prior art has problems in the preparation of high-entropy boronide ultra-high temperature ceramics that damage the properties of oxidative impurities and uneven composition or microstructure when carbon black is used as a carbon source.

Method used

Using the liquid phase method, transition metal oxides are used as metal source, boric acid is used as boron source, and sorbitol is used as carbon source, combined with boron thermal/carbon thermal reduction reaction, through acrylamide, N,N'-methylenebisacrylamide, Ammonium sulfate and tetramethylethylenediamine were gelled to prepare high entropy boronide ultra-high temperature ceramic powder.

Benefits of technology

The preparation of green, low-cost and controllable high-entropy boronide ultra-high temperature ceramic powder is achieved, ensuring the composition uniformity of the finished product and the optimization of the microstructure, and improving the performance of the ceramic.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430950A_ABST
    Figure CN119430950A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing high-entropy boride ultrahigh-temperature ceramic powder by a liquid phase method. The green, low-cost and controllable high-entropy boride superhigh-temperature ceramic powder is prepared by taking a transition metal oxide as a metal source, boric acid as a boron source and sorbitol as a carbon source through a liquid phase method in combination with a boron thermal / carbon thermal reduction reaction. According to the preparation method disclosed by the invention, the ammonium sulfate, the tetramethylethylenediamine, the acrylamide and the N, N '-methylene bisacrylamide are used for carrying out gelation treatment to obtain the pure-phase high-entropy boride ultrahigh-temperature ceramic powder, so that a feasible strategy is provided for preparing the high-entropy boride ultrahigh-temperature ceramic powder which is efficient, environment-friendly and economical.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a method for preparing high-entropy boride ultra-high temperature ceramic powder by a liquid phase method. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Ultra-high temperature ceramics refer to a class of ceramic materials that can maintain stable physical and chemical properties in harsh environments such as ultra-high temperatures (≥2000℃) and reaction atmospheres, mainly including refractory metal carbides, borides, nitrides, etc. Transition metal diborides are a class of ceramic materials with excellent ultra-high temperature performance. Usually composed of transition metals and boron elements, they show significantly high melting points, excellent thermal stability and extremely high hardness, but still have problems such as low fracture toughness and insufficient oxidation resistance at ultra-high temperatures. High entropy boride ultra-high temperature ceramics are a class of ceramic materials composed of multiple transition metal elements and boron elements, and their core characteristic is the high entropy effect. This effect originates from the presence of four or more (including four) metal elements in the material, which exist in equimolar ratios to form a solid solution with a high degree of mixed components. Due to the high entropy effect, hysteresis diffusion effect, lattice distortion effect and cocktail effect, high entropy transition metal diboride ceramics have more excellent properties, such as higher hardness and better oxidation resistance. These properties enable high-entropy transition metal diborides to exhibit excellent wear resistance and oxidation resistance in high temperature and high stress environments. Through precise synthesis and processing techniques, they can be used to manufacture key components such as ultra-high temperature tools, nozzles, thermal protection systems, and are used in aerospace, national defense, metallurgy and other fields.

[0004] In the preparation of high-entropy boride ultra-high temperature ceramic blocks, single-component transition metal borides are usually used as raw materials, mechanically mixed in the form of high-energy ball milling, and then hot-pressed sintering or spark plasma sintering. However, the presence of oxidative impurities will impair the performance. In addition, boron thermal / carbon thermal reduction reactions using transition metal oxide powders, boron carbide, carbon black, etc. as raw materials are a promising low-cost method for preparing bulk high-entropy boride ultra-high temperature ceramics. However, when carbon black is selected as the carbon source, it cannot be guaranteed to be fully in contact with the oxide powder, and the resulting product may be uneven in composition or microstructure. The advantage of the liquid phase method is that the starting materials can be uniformly mixed at the molecular level. It is necessary to choose a liquid phase method to prepare high-entropy ultra-high temperature ceramic powders. Traditional work uses transition metal chlorides or organic precursors as metal sources, furfural, acetylacetone or blended allyl functional new polymer resins as carbon sources, and adopts a liquid polymer precursor route to prepare high-entropy ultra-high temperature ceramic powders with uniform element distribution. However, the transition metal chlorides or organic precursors used in the above methods are more expensive than transition metal oxides. Furfural, acetylacetone or blended allyl functional new polymer resins also increase the synthesis cost compared to biomass sugars such as sorbitol, which is not environmentally friendly. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing high entropy boride ultra-high temperature ceramic powder by a liquid phase method.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0009] TiO 2 、ZrO 2 , HfO 2 , Nb 2 O 5 and Ta 2 O 5 The powders were mixed evenly to obtain mixture I, and ZrO 2 Ball milling beads and ethanol, and then drying to obtain a mixed powder;

[0010] Boric acid and sorbitol are dissolved in water to obtain solution Ⅰ;

[0011] Acrylamide and N,N'-methylenebisacrylamide are added to solution I, stirred evenly, and ammonia water is added to adjust the pH to obtain solution II;

[0012] The mixed powder is added to solution II, and after being evenly dispersed, ammonium persulfate and tetramethylethylenediamine are added for gelation treatment to obtain a gel, which is heated to remove moisture, and then heat-treated in an inert atmosphere to obtain a carbonized sample;

[0013] The carbonized sample is crushed, sintered in an inert atmosphere, and naturally cooled to obtain a high-entropy boride ultrahigh temperature ceramic powder.

[0014] As a preferred embodiment of the method for preparing high entropy boride ultra-high temperature ceramic powder by a liquid phase method according to the present invention, wherein: in the mixture I, TiO 2 、ZrO 2 , HfO 2 , Nb 2 O 5 、 2 O 5 The molar ratio is 2:2:2:1:1~1.1, and the particle size is <10μm.

[0015] As a preferred scheme of the method for preparing high entropy boride ultra-high temperature ceramic powder by a liquid phase method described in the present invention, the mass ratio of the ethanol to the mixed powder is 1 to 5:1, the ball milling speed is 200 to 300 r / min, and the time is 12 to 24 h.

[0016] As a preferred solution of the method for preparing high entropy boride ultra-high temperature ceramic powder by liquid phase method of the present invention, wherein: the ZrO 2 The diameter of the ball milling beads is 1 to 10 mm, and the mass ratio of the ball milling beads to the mixed powder is 2 to 10:1.

[0017] As a preferred embodiment of the method for preparing high entropy boride ultra-high temperature ceramic powder by a liquid phase method described in the present invention, the molar ratio of the boric acid, sorbitol and mixture I is 20-30:9-15:2.

[0018] As a preferred embodiment of the method for preparing high entropy boride ultra-high temperature ceramic powder by a liquid phase method described in the present invention, the concentration of acrylamide in solution II is 0.3-0.5 g / L, and the mass ratio of acrylamide to N,N'-methylenebisacrylamide is 10-15:1.

[0019] As a preferred embodiment of the method for preparing high entropy boride ultra-high temperature ceramic powder by a liquid phase method of the present invention, the concentration of the mixed powder in solution II is 0.1-0.5 g / mL.

[0020] As a preferred solution of the method for preparing high entropy boride ultra-high temperature ceramic powder by a liquid phase method described in the present invention, wherein: the adding of ammonia water to adjust the pH is to adjust the pH to 8-9.

[0021] As a preferred embodiment of the method for preparing high entropy boride ultra-high temperature ceramic powder by a liquid phase method described in the present invention, the mass ratio of ammonium persulfate to tetramethylethylenediamine is 1:1-1.2, and the concentration of ammonium persulfate in solution II is 0.8-1.0 g / L.

[0022] As a preferred embodiment of the method for preparing high entropy boride ultra-high temperature ceramic powder by a liquid phase method of the present invention, wherein: the inert atmosphere is nitrogen or argon, the heat treatment temperature is 500-600°C, and the holding time is 1-2 hours; the sintering temperature is 2000-3000°C, and the holding time is 1-4 hours. Beneficial effects of the present invention:

[0023] (1) The present invention uses transition metal oxide as a metal source, boric acid as a boron source, and sorbitol as a carbon source, and adopts a liquid phase method combined with boron thermal / carbon thermal reduction reaction to prepare a green, low-cost, controllable high-entropy boride ultra-high temperature ceramic powder;

[0024] (2) The present invention uses ammonium sulfate, tetramethylethylenediamine, acrylamide, and N,N'-methylenebisacrylamide for gelation treatment to successfully synthesize pure phase high entropy boride ultra-high temperature ceramic powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments and comparative examples. Obviously, the drawings described below are only some embodiments and comparative examples of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0026] Figure 1 The high entropy (Ti) prepared in Example 1 of the present invention 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B 2 X-ray diffraction pattern of powder.

[0027] Figure 2 The high entropy (Ti) prepared in Example 1 of the present invention 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B 2 Scanning electron microscope image of the powder.

[0028] Figure 3 This is the X-ray diffraction pattern of the powder prepared at 1900°C in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0032] The raw materials used in the present invention are all commonly available in the market unless otherwise specified.

[0033] Example 1

[0034] This embodiment provides a method for preparing high entropy boride ultra-high temperature ceramic powder by a liquid phase method.

[0035] 1) TiO 2 、ZrO 2 , HfO 2 , Nb 2 O 5 and Ta 2 O 5 Five kinds of transition metal oxide powders were mixed in a molar ratio of 2:2:2:1:1, with the masses of 1.5976g, 2.4646g, 4.2140g, 2.6608g, and 4.4233g, respectively. The particle sizes were all less than 10μm, and the total oxide powder was about 15.36g. The mixed powder was poured into a ball mill, and 30g of 5mm diameter ZrO 2 Ball mill beads, ZrO 2 The mass ratio of ball milling beads to mixed powder is 2:1, 20 mL of ethanol is added, and the mass ratio of ethanol to mixed powder is 4:3, and the ball milling is performed at a speed of 250 rpm for 12 h; the ethanol is removed in an oven at 80°C, and the transition metal oxide mixed powder is collected;

[0036] 2) Add 0.3 mol of boric acid and 0.15 mol of sorbitol to 100 mL of deionized water, with the molar ratio of boric acid, sorbitol to the mixed powder being 10:5:1, and stir at 60°C until dissolved to obtain solution I;

[0037] 3) Add 30 g acrylamide and 2 g N,N'-methylenebisacrylamide to solution I. The concentrations of acrylamide and N,N'-methylenebisacrylamide in solution II are 0.3 g / mL and 0.02 g / mL, respectively, and the mass ratio of the two is 15:1. Add ammonia water dropwise to adjust the pH of the solution to 9 to obtain solution II.

[0038] 4) Add the mixed powder to 150 mL of solution II, the mixed powder concentration is 0.1 g / mL, ultrasonicate for 10 minutes, stir for 20 minutes, add 0.12 g of ammonium persulfate and 0.12 g of tetramethylethylenediamine, the concentrations of which in solution II are both 0.8 g / L, continue stirring to achieve gelation, transfer the gel to a 120°C oven and keep it warm for 10 hours to remove moisture, then place it in a tubular furnace for heat treatment, pass argon, heat to 600°C at a rate of 10°C / min, keep it warm for 2 hours, and naturally cool to room temperature to obtain a carbonized sample.

[0039] 5) The carbonized sample was crushed and placed in a graphite crucible, placed in a high-temperature atmosphere furnace, and argon was passed through. The temperature was raised to 2000°C at a rate of 10°C / min for sintering. The sample was kept at this temperature for 1 hour and naturally cooled to room temperature to obtain a high-entropy boride ultrahigh temperature ceramic powder, which was recorded as (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B 2 .

[0040] Figure 1 for (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B 2 The X-ray diffraction pattern of the powder shows that the product has achieved sufficient high entropy; Figure 2 for (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B 2 Scanning electron microscope image of the powder.

[0041] Example 2

[0042] The difference between this embodiment and embodiment 1 is that the sintering temperature in step 5) is adjusted to 3000° C., and the other steps are the same as those in embodiment 1 to obtain a high entropy boride ultra-high temperature ceramic powder.

[0043] Example 3

[0044] The difference between this embodiment and embodiment 1 is that in step 3), the concentration of acrylamide in solution II is adjusted to 0.5 g / mL, and the concentration of N,N'-methylenebisacrylamide in solution II is adjusted to 0.05 g / mL, and the mass ratio of the two is 10:1. The other steps are the same as those in embodiment 1, and a high entropy boride ultrahigh temperature ceramic powder is obtained.

[0045] Comparative Example 1

[0046] The difference from Example 1 is that the amount of boric acid in step 2) is adjusted to 0.2 mol, and the other steps are the same as Example 1.

[0047] Carbides appear in the product and high entropy boride ceramic powder cannot be obtained.

[0048] The acquisition of the high entropy boride of the present invention depends on the chemical reaction of oxide, carbon source and boron source to generate boride at high temperature. As a boron source, boric acid decomposes at high temperature to produce boron oxide, which volatilizes at high temperature, so an excess of boron source is required in the actual reaction. In the case where the content of boric acid is insufficient but the carbon source is sufficient, the chemical reaction of the product high entropy boride cannot fully occur, and the residual carbon source reacts with the residual oxide to generate carbide impurities.

[0049] Comparative Example 2

[0050] The difference from Example 1 is that the amount of sorbitol in step 2) is adjusted to 0.1 mol, and the other steps are the same as in Example 1.

[0051] Some oxides remain in the product and high entropy boride ceramic powder cannot be obtained.

[0052] The acquisition of the high entropy boride of the present invention depends on the chemical reaction of the oxide, carbon source and boron source to generate the boride at high temperature. As a carbon source, sorbitol decomposes at high temperature to produce carbon. In the case of insufficient carbon content, the chemical reaction of the product high entropy boride cannot fully occur, and finally unreacted oxide remains.

[0053] Comparative Example 3

[0054] The difference from Example 1 is that in step 3), acrylamide or N,N'-methylenebisacrylamide is not added, and the other steps are the same as Example 1.

[0055] The solution remains in liquid state and does not gel, so high-entropy boride ceramic powder cannot be obtained.

[0056] Comparative Example 4

[0057] The difference from Example 1 is that in step 3), no ammonia water is added to adjust the pH, and the other steps are the same as Example 1.

[0058] The solution remains in liquid state for a long time, making it difficult to achieve gelation and thus it is impossible to obtain high entropy boride ceramic powder.

[0059] Only through gelation can the ceramic powder be evenly mixed with the carbon source, boron source, etc., and only after gelation can subsequent carbonization and sintering steps be carried out to obtain high-entropy boride ceramic powder.

[0060] Comparative Example 5

[0061] The difference from Example 1 is that in step 4), no ammonium persulfate or tetramethylethylenediamine is added, and the other steps are the same as Example 1.

[0062] The solution remains in liquid state and does not gel, so high-entropy boride ceramic powder cannot be obtained.

[0063] Comparative Example 6

[0064] The difference from Example 1 is that the sintering temperature in step 5) is adjusted to 1900° C., and the other steps are the same as Example 1.

[0065] Figure 3 This is the XRD test result. It can be seen that the phase is mainly a high-entropy diboride ceramic phase, and there is a phase that is not fully high-entropy.

[0066] Compared with Example 1, the compound in this comparative example has a ceramic phase that is not fully high-entropy, so controlling the sintering temperature is crucial in preparing high-entropy boride ultra-high temperature ceramic powder.

[0067] In summary, the present invention uses transition metal oxide as metal source, boric acid as boron source, sorbitol as carbon source, and adopts liquid phase method combined with boron thermal / carbon thermal reduction reaction to prepare green, low-cost, controllable high-entropy boride ultra-high temperature ceramic powder; the present invention uses ammonium sulfate, tetramethylethylenediamine, acrylamide, and N,N'-methylenebisacrylamide for gelation treatment to successfully synthesize pure phase high-entropy boride ultra-high temperature ceramic nanopowder.

[0068] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing high entropy boride ultra-high temperature ceramic powder by a liquid phase method, characterized in that: include, TiO2, ZrO2, HfO2, Nb2O5 and Ta2O5 powders are uniformly mixed to obtain mixture I, and ZrO2 ball milling beads and ethanol are added, and mixed powders are obtained after ball milling and drying; Boric acid and sorbitol are dissolved in water to obtain solution Ⅰ; Acrylamide and N,N'-methylenebisacrylamide are added to solution I, stirred evenly, and ammonia water is added to adjust the pH to obtain solution II; The mixed powder is added to solution II, and after being evenly dispersed, ammonium persulfate and tetramethylethylenediamine are added for gelation treatment to obtain a gel, which is heated to remove moisture, and then heat-treated in an inert atmosphere to obtain a carbonized sample; The carbonized sample is crushed, sintered in an inert atmosphere, and naturally cooled to obtain a high-entropy boride ultrahigh temperature ceramic powder.

2. The method for preparing high entropy boride ultra-high temperature ceramic powder by liquid phase method according to claim 1, characterized in that: In the mixture I, the molar ratio of TiO2, ZrO2, HfO2, Nb2O5 and Ta2O5 is 2:2:2:1:1-1.1, and the particle sizes are all less than 10 μm.

3. The method for preparing high entropy boride ultra-high temperature ceramic powder by liquid phase method according to claim 1, characterized in that: The mass ratio of the ethanol to the mixed powder is 1-5:1, the rotation speed of the ball mill is 200-300 r / min, and the time is 12-24 hours.

4. The method for preparing high entropy boride ultra-high temperature ceramic powder by liquid phase method according to claim 1, characterized in that: The diameter of the ZrO2 ball milling beads is 1 to 10 mm, and the mass ratio of the ZrO2 ball milling beads to the mixed powder is 2 to 10:

1.

5. The method for preparing high entropy boride ultra-high temperature ceramic powder by liquid phase method according to claim 1, characterized in that: The molar ratio of the boric acid, sorbitol and the mixed powder is 20-30:9-15:

2.

6. The method for preparing high entropy boride ultra-high temperature ceramic powder by liquid phase method according to claim 1, characterized in that: The concentration of the acrylamide in solution II is 0.3-0.5 g / L, and the mass ratio of the acrylamide to N,N'-methylenebisacrylamide is 10-15:

1.

7. The method for preparing high entropy boride ultra-high temperature ceramic powder by liquid phase method according to claim 1, characterized in that: The concentration of the mixed powder in solution II is 0.1-0.5 g / mL.

8. The method for preparing high entropy boride ultra-high temperature ceramic powder by liquid phase method according to claim 1, characterized in that: The step of adding ammonia water to adjust the pH is to adjust the pH to 8-9.

9. The method for preparing high entropy boride ultra-high temperature ceramic powder by liquid phase method according to claim 1, characterized in that: The mass ratio of the ammonium persulfate to tetramethylethylenediamine is 1:1-1.2, and the concentration of the ammonium persulfate in solution II is 0.8-1.0 g / L.

10. The method for preparing high entropy boride ultra-high temperature ceramic powder by liquid phase method according to claim 1, characterized in that: The inert atmosphere is nitrogen or argon, the heat treatment temperature is 500-600°C, and the insulation time is 1-2 hours; the sintering temperature is 2000-3000°C, and the insulation time is 1-4 hours.

Citation Information

Patent Citations

  • High-entropy oxide submicron powder and preparation method thereof

    CN110903084A

  • Preparation method of high-entropy boride infrared radiation material

    CN117466650A

  • Method for producing high-entropy alloy boride

    RU2804391C1

  • Dual Phase High Entropy Boride-Carbide Composites for Extreme Environments

    US20240287657A1

  • Method for obtaining a high-entropy oxide

    WO2023099855A1

Cited By

  • Complex-phase high-entropy ceramic as well as preparation method and application thereof

    CN119930298A